2019
DOI: 10.5937/engrami1902021j
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in special education teachers working with children with developmental disorders

Abstract: Engrami· vol. 41 · jul-decembar 2019. · br. 2 21 Kratak sadržaj Uvod. Brojna istraživanja u svetu i kod nas su pokazala da su osobe koje se profesionalno bave pružanjem pomoći drugim ljudima i koje pripadaju tzv. "pomagačkim profesijama" (zdravstveni radnici, psiholozi, pedagozi, socijalni radnici, nastavnici itd.) pod visokim rizikom za razvijanje različitih psihofizičkih stresnih reakcija i simptoma sindroma izgaranja. Sindrom izgaranja se danas posmatra kao društveni i profesionalni problem, a ne samo kao o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Nevertheless, there seems to be some variation among special education teachers. For example, the work by Jovanović, Karić, Mihajlović, Džamonja-Ignjatović, and Hinić (2019) found that emotional exhaustion, depersonalization, and lack of personal accomplishment are high for special education teachers who work with children with motor skill disorders and low in teachers working with intellectually disabled children or students with social behavior problems. The high levels of burnout in special education teachers seem to be related to the characteristics of their work, as indicated by a mixed-method study by Garwood, Werts, Varghese, and Gosey (2018): data collected from special education teachers suggested that the lack of clarity of their role, excessive facets to their roles, emotional exhaustion, and lack of accomplishment may contribute to their perception of stress and burnout.…”
Section: Personal and Professional Factors Related To Teachers' Burnoutmentioning
confidence: 99%
“…Nevertheless, there seems to be some variation among special education teachers. For example, the work by Jovanović, Karić, Mihajlović, Džamonja-Ignjatović, and Hinić (2019) found that emotional exhaustion, depersonalization, and lack of personal accomplishment are high for special education teachers who work with children with motor skill disorders and low in teachers working with intellectually disabled children or students with social behavior problems. The high levels of burnout in special education teachers seem to be related to the characteristics of their work, as indicated by a mixed-method study by Garwood, Werts, Varghese, and Gosey (2018): data collected from special education teachers suggested that the lack of clarity of their role, excessive facets to their roles, emotional exhaustion, and lack of accomplishment may contribute to their perception of stress and burnout.…”
Section: Personal and Professional Factors Related To Teachers' Burnoutmentioning
confidence: 99%